Utilização de simulação termodinâmica para desenvolvimento de aços inoxidáveis modificados com boro conformados por spray : aplicações e limitações - Lopes, Thiago Pama (Universidade Federal de São Carlos, 2017)
Stainless steels are outstanding candidates for applications in the oil exploitation at the pre-salt layer in Brazil since they have an excellent combination of mechanical and corrosion properties. Nevertheless, they have questionable wear resistance in case of more severe application conditions. Recent alloy developments from DEMa-UFSCar adopted a strategy based on boron additions to stainless steel processed by spray forming (SF). Boron additions lead to the formation of hard metallic borides and, in turn, improve the wear resistance. However, boride formation also induces other microstructural changes that, up to now, have not been systematically investigated. Additionally, recently proposed solidification models of spray-formed Fe-based alloys indicate that solidification in the deposition zone tends to follow the thermodynamic equilibrium. Consequently, this present work proposes a methodology employing a computational thermodynamic tool with the ultimate goal of developing Fe-based alloys with boron additions prepared by spray forming. This work focused on spray-formed duplex stainless steels modified with boron (AIDM) containing a hypoeutectic composition with a duplex matrix. The thermodynamic software (Thermo-Calc® 4.0) with the TCFe7 database was used. Firstly, experimental results of the superduplex and ferritic modified stainless steels with boron already described in the literature were used for validation of the computational tool. After this step, a methodology for the thermodynamic simulation was proposed aiming at finding a chemical composition that should lead to specific pre-established microstructural features in the AIDM. As means of experimental validation for the proposed methodology, the selected chemical composition was prepared by spray forming and the microstructure investigated. The results showed that all pre-established microstructural features were indeed achieved thus supporting the proposed methodology for alloy design. Therefore the application of computational thermodynamics seems to be an excellent resource for designing spray-forming boron-modified stainless steels.
The application of thermodynamic simulations to develop of stainless steel modified with boron spray forming : limitations and aplications
Keywords: Aço inoxidável; Conformação por spray; Projeto de liga; Boro; Stainless steel; Spray forming; Alloy design; Boron; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA